2D AlN Layers Sandwiched Between Graphene and Si Substrates. Issue 2 (4th November 2018) - Wang, Wenliang; Zheng, Yulin; Li, Xiaochan; Li, Yuan; Zhao, Hui; Huang, Liegen; Yang, Zhichao; Zhang, Xiaona; Li, Guoqiang
Abstract: Due to the superior thickness‐dependent properties, 2D materials have exhibited great potential for applications in next‐generation optoelectronic devices. Despite the significant progress that has been achieved, the synthesis of 2D AlN remains challenging. This work reports on the epitaxial growth of 2D AlN layers via utilizing physically transferred graphene on Si substrates by metal–organic chemical vapor deposition. The 2D AlN layers sandwiched between graphene and Si substrates are confirmed by annular bright‐field scanning transmission electron microscopy and the effect of hydrogenation on the formation of 2D AlN layers is clarified by theoretical calculations with first‐principles calculations based on density functional theory. Moreover, the bandgap of as‐grown 2D AlN layers is theoretically predicted to be ≈9.63 eV and is experimentally determined to be 9.20–9.60 eV. This ultrawide bandgap semiconductor shows great promise in deep‐ultraviolet optoelectronic applications. These results are expected to support innovative and front‐end development of optoelectronic devices. Abstract : The epitaxial growth of 2D AlN layers via utilizing physically transferred graphene on Si substrates by metal–organic chemical vapor deposition is reported. The bandgap of as‐grown 2D AlN layers is theoretically predicted to be ≈9.63 eV and is experimentally determined to be 9.20–9.60 eV.